If it's not what You are looking for type in the equation solver your own equation and let us solve it.
t+10=7t-1
We move all terms to the left:
t+10-(7t-1)=0
We get rid of parentheses
t-7t+1+10=0
We add all the numbers together, and all the variables
-6t+11=0
We move all terms containing t to the left, all other terms to the right
-6t=-11
t=-11/-6
t=1+5/6
| -2(7+7x)=84 | | 11u-9+3u=-123 | | 9+-5c=5 | | 5x-8x+16=41 | | 5(x-)=20(x-10) | | k÷4=36 | | 3x+4+8x+2=39 | | 3x+2(3x-5)=-73 | | -y+60=223 | | 3x+5=5x–9 | | 8b=72= | | 8−x=21 | | 5x+2=166 | | 7x+3(5-3x)=6 | | 7x-4=161 | | -2(m+4)=-8 | | x+(x+1)+(x+2)=-84 | | 163-w=256 | | 2/3w+1/6+1/2w=34 | | -3(8k+8)-4k=-108 | | -21=3v-4 | | 15x-90=4x-7 | | 3p-8=p-3 | | 62+67+x=180 | | 166=40-x | | 144=16x-16 | | 3/4w+1/6+1/2w=3/4 | | -55=-5(9+p) | | 3/4w+1/6+1/2w=34 | | -24-6x=24 | | 3x-4+2x+9=-20 | | 7p+6=-8 |